A Review on 3D Printing Processes, Materials, Process Parameters and Applications - Pandey, Rohit (Recent Advances in Mechanical Engineering, 2024)
Additive manufacturing’s ability to create highly complex geometric forms has had a huge impact on the world today. The practical use of 3D plastic objects is limited by their anisotropy and poor properties. Adding fillers improves application versatility and performance. The advantages of 3D printing include low labour costs, low cost and ease of editing and modifying drawings. He specialises in additive manufacturing (AM), fused deposition modelling (FDM), powder-liquid 3D printing (PLP), virtual light processing (DLP), stereolithography (SLA), selective laser sintering (SLS) and electron beam melting. Studies have shown that many parameters such as angle, die tip, feed speed, scanning angle, extruder temperature and plate spacing affect the product delivered. Various methods have been proposed to improve these parameters. To choose the best sign for your chosen software, it will be useful to analyse the main features, advantages and disadvantages of the season. Likewise, research in these areas will further improve the performance of 3D printing projects.
uGDX